O‘ZBEKISTON TURIZM ALOQALARINING JAHON TURIZM BILAN BOG‘LIQLIGI - Ismoilova Maftuna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: The article based on the World Tourism Organization (UNWTO) data and a number of other organizations. There is considered changes in the tourism sector, in particular, it analyzes in detail the shifts in the number of tourists coming to Uzbekistan and other countries, their causes and factors. Despite the worsening geopolitical situation, the flow of foreign tourists is increasing.